PENGARUH SOCIAL MEDIA MARKETING, GAYAHIDUP, PENGETAHUAN PRODUK TERHADAP KEPUTUSAN PEMBELIANKOPI JANJI JIWA DENGAN NIAT BELI SEBAGAI VARIABEL MEDIASI - Putri, Asri Qomariyati; Daulay, M Yasser Iqbal (UNIB Press, 2026)
Coffee is a drink that has a distinctive aroma, taste and popular with various groups. One of the best coffee shops is Kopi Janji Jiwa. One of them is in the city of Bengkulu, which is located on Jalan Sutoyo No 08 Tanah Patah, Ratu Agung District. This study aims to look at the influence of social media marketing, lifestyle and product knowledge on purchasing decisions for Janji Jiwa coffee in the city of Bengkulu. This study uses three independent variables, namely lifestyle, product knowledge, and social media marketing, one dependent variable, namely purchasing decisions and a mediating variable, namely purchase intention. This study uses quantitative methods, the type of data used is primary data. Data was collected through a questionnaire which was distributed online to 210 respondents who live in Bengkulu and have purchased a copy of Janji Jiwa in the city of Bengkulu. The results of this study indicate that lifestyle variables have no effect and are not significant on purchase intention. Lifestyle has no effect and is not signif icant on purchasing decisions. Purchase intention has significant influence on purchasing decisions. Product knowledge has significant and significant effect on purchase intention. Product knowledge has a significant and influential effect on purchasing decisions. Social media marketing has significant and significant effect on purchase intention. Social media marketing has an influence and is significant on purchasing decisions. Keywords: lifestyle, product knowledge, social media marketing, purchase intention, purchase decision